Why Children’s Suggestibility Remains a Serious Concern - Marsil, Dorothy F. (Law and contemporary problems, 2002)
Warren and Marsil focus on six areas representing some of the most intractable problems that will require further attention from scientists and practitioners alike. Research on child witnesses is highlighted, concentrating primarily on studies published or presented in the past ten years